Subjective imputation of a possible type of fraud in the Thomas Restobar case - Sisniegas Rodríguez, Roger (2020)
In the following lines, a case of legal-criminal relevance will be analyzed, which occurred in Peru when the COVID-19 pandemic was going through and during the State of Emergency. Thirteen young people died inside a nightclub that worked with more than one hundred and twenty attendees, this tragedy recalled several similar cases that shocked the country. For this objective, the analysis of using the national doctrine and the personal position of the author is used, also, it is addressed, among other legal-criminal and social problems that the fatal event triggered.